Effect of reconstructive vascular surgery on red cell deformability–preliminary results. Issue 10 (October 1983) - Irwin, S T; Rocks, M J; McGuigan, J A; Patterson, C C; Morris, T C; O'Reilly, M J
Abstract : Using a simple filtration method, red cell deformability was measured in healthy control subjects and in patients with peripheral vascular disease. Impaired red cell deformability was demonstrated in patients with rest pain or gangrene and in patients with intermittent claudication. An improvement in red cell deformability was demonstrated after successful reconstructive vascular surgery in both patient groups. An improvement in red cell deformability was demonstrated in patients undergoing major limb amputation.